The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1249/mss.0000000000001369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Altering Trunk Position during Landings on Patellar Tendon Force and Pain

Abstract: Landing with greater trunk flexion decreased patellar tendon force in elite jumping athletes. An immediate decrease in knee pain was also observed in symptomatic athletes with a more flexed trunk position during landing. Increasing trunk flexion during landing might be an important strategy to reduce tendon overload in jumping athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 55 publications
3
61
1
Order By: Relevance
“…Participants in this study displayed a similar knee flexion angle at IC and a hip extension strategy during landing contrary to the hypothesis. Lack of difference in knee flexion angle at IC between PT and controls aligns with previous research in adult PT cohorts during drop landings and a spike jump landing . However, this study's finding contradicts a significantly greater knee flexion angle at IC reported in asymptomatic PTA cohorts, adults and sub‐elite junior basketballers during the horizontal phase of a stop‐jump.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Participants in this study displayed a similar knee flexion angle at IC and a hip extension strategy during landing contrary to the hypothesis. Lack of difference in knee flexion angle at IC between PT and controls aligns with previous research in adult PT cohorts during drop landings and a spike jump landing . However, this study's finding contradicts a significantly greater knee flexion angle at IC reported in asymptomatic PTA cohorts, adults and sub‐elite junior basketballers during the horizontal phase of a stop‐jump.…”
Section: Discussionsupporting
confidence: 73%
“…The disparity of kinematic findings in this study in comparison with other landing studies may partially be explained by varied cohorts (age, sport, skill level, injury history/current) and jump‐landing task selection (stop‐jump horizontal landing, spike jump landing, drop landing). Most of the previous research investigating PT and landing kinematics has focused upon a vertical landing phase; however, in comparison athletes adopt a different movement strategy in a horizontal landing phase . The differences of kinematic findings between studies and differences in landing strategies between vertical and horizontal tasks supports the idea of contextually specific landing mechanics.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations